Paedophilia and other types of sexual abuse on minors. - Ciccone, Lino (Medicina e Morale, 2003)
The author, after have underlined the presence of several issues about paedophilia, dedicates the first part of the article to the phenomenology of this behaviour in its various aspects, enclosed the attention given to it in the civil society and in the Church. Then, the A. tackles the specific ethical issues, according to tested distinction between objective morality and subjective responsibility. The contribution dwells about the operative field, also giving practical indications. Finally, the A. dedicates some considerations to the crucial problem of the attributed diffusion of the paedophilia in the catholic clergy in some countries.